Measurement of the helicity dependence for single π0 photoproduction from the deuteron; The European Physical Journal A - Hadrons and Nuclei; Vol. 58, iss. 6 - Cividini F.; Dieterle M. Manuel; Abt S.; Achenbach P.; Adlarson P.; Annand J. R. M.; Fiks (Fix) A. I. Alexander Ivanovich (2022, 2022)
Title screen